GIRL CHILD EDUCATION: A THREAT TO THE HEALTH RELATED MILLENNIUM DEVELOPMENT GOALS - Jokthan, Esrom Toro (Sokoto Educational Review, 2020)
World leaders have agreed to create opportunity for the provision of quality education for all its citizens. This was after The World Conference on Education for All (EFA), 1990 and The Daka Framework for Action, 2000. Nigeria Policy on Education submits that every child shall have a right to equal educational opportunities irrespective of any real or imagined disability. The Education for All (EFA), Dakar Framework for Action, (DFA) and 7Point Agenda (7PA) of Nigeria's President Musa Umaru Yar’Adua are complementary to the MDGs eight goals all to be achieved by year 2015. Goals 4 to 6 of the MDGs are health related (Reduce Child Mortality; Improve Maternal Health and Combat HIV/AIDS, Malaria and other Diseases). The girl child, a citizen of the world, does not seem to benefit from due to low enrollment and retention in schools. Evidence abound that educating girls is essential factor towards making societies healthier, wealthier and safer. However, some of them end up as street girls. The street provides numerous dangers to her health and social wellbeing. There are evidences that education is a potent instrument if given, the girl child can scale over the dangers posed to her health. The paper concluded by giving the contribution of Gombe State University to girl child education.